Growth Inhibitory Properties of Kunzea pomifera F.Muell. and Podocarpus elatus R.Br. Fruit Extracts against Axillary and Foot Odour Producing Bacteria - Wood, Aiden; Cock, Ian Edwin (Asian Journal of Biological and Life Sciences)
Introduction: Many high antioxidant fruit extracts can inhibit the growth of multiple bacterial pathogens. They may also inhibit the growth of malodour producing bacteria and thus be useful deodorant components, although this is yet to be tested for many Australian native fruits. Materials and Methods : Methanolic and aqueous K. pomifera and P. elatus fruit extracts were investigated by disc diffusion and liquid dilution MIC assays against the most significant bacterial contributors to axillary and plantar malodour. Toxicity was determined using Artemia franciscana nauplii bioassays and unbiased HPLC-MS QTOF analysis was used to identify interesting consituents of the most active extract. Results: Methanolic and aqueous K. pomifera and P. elatus fruit extracts displayed noteworthy bacterial growth inhibitory activity against all of the malodour forming bacteria tested. The methanolic K. pomifera extract had particularly good antibacterial effects, strongly inhibiting the growth of all bacteria, with MIC values substantially less than 1000 μg/mL. Indeed, liquid dilution (LD) MIC values of 610, 894, 663 and 625 μg/mL were recorded against C. jeikeium, P. acnes, B. linens and S. epidermidis respectively. Similar, albeit slightly higher LD MIC values were noted for the aqueous K. pomifera fruit extract, and for the methanolic and aqueous P. elatus fruit extracts against these bacteria. All K. pomifera and P. elatus fruit extracts were non-toxic in the Artemia fransiscana bioassay. Several interesting phytochemicals, including several tannins, were identified in the methanolic K. pomifera fruit extract. Conclusion: The lack of toxicity of the methanolic and aqueous K. pomifera and P. elatus fruit extracts and their noteworthy growth inhibition of axillary and plantar malodour producing bacteria indicate their potential as deodorant components. Further studies are warranted to isolate and identify the active components and to determine the antibacterial mechanism.
Keywords: Muntries; Illawarra plum; Body odour; Deodorant; Corneybacterium jeikeium; Propionobacter acnes; Brevibacter linens; Staphylococcus epidermidis.